Using the realistic mathematics education (RME) approach with scaffolding to enhance mathematical representation ability - Putra, Rizki Wahyu Yunian; Sutiarso, Sugeng; Nurhanurawati, Nurhanurawati (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Mathematical representation skills are essential for understanding and applying mathematical concepts. However, many students struggle to connect abstract concepts to real-life situations, making it difficult for them to improve their representation skills.Aim: This study aims to develop and test the effectiveness of the Realistic Mathematics Education (RME) approach, supported by scaffolding, in improving students' mathematical representation skills.Method: The study followed the ADDIE model, which includes five steps: Analysis, Design, Development, Implementation, and Evaluation. The participants were 50 second-semester students from classes A, C, and D in the Mathematics Education program at UIN Raden Intan Lampung.Results: The development of the Realistic Mathematics Education (RME) model with scaffolding was validated by eight expert validators, confirming its validity and practicality. The model was designed to align with learning objectives, incorporate real-world contexts, and provide structured scaffolding tailored to students’ needs. During implementation, the model demonstrated practicality as students actively engaged with learning activities and gradually developed independence in problem-solving. The effect size calculation of 0.9, categorized as high, confirmed the model’s effectiveness in significantly enhancing students' mathematical representation skills.Conclusion: The RME approach with scaffolding is an effective method to improve the quality of mathematics learning in higher education. It helps students better understand and apply mathematical concepts by linking them to practical problems.